2021
DOI: 10.1093/treephys/tpab044
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling resilience mechanisms in forests: role of non-structural carbohydrates in responding to extreme weather events

Abstract: Extreme weather events are increasing in frequency and intensity due to global climate change. We hypothesized that tree carbon reserves are crucial for resilience of beech, buffering the source-sink imbalance due to late frosts and summer droughts, and that different components of non-structural carbohydrates (NSCs) play specific roles in coping with stressful situations. To assess the compound effects on mature trees of two extreme weather events, first a late frost in spring 2016 and then a drought in summe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Our results might sound optimistic, especially for beech for which drought-induced growth decline has been observed at the southern edge of their distribution area (Charru et al, 2010;Zimmermann et al, 2015;D'Andrea et al, 2020aD'Andrea et al, , 2020b, raising concern about their persistence under warmer and drier conditions (Noce et al, 2017). However, other studies point out opposite results (Tegel et al, 2014) or emphasize the swift recovery ability of beech after drought episodes (Vanhellemont et al, 2019).…”
Section: Impact On Nppmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results might sound optimistic, especially for beech for which drought-induced growth decline has been observed at the southern edge of their distribution area (Charru et al, 2010;Zimmermann et al, 2015;D'Andrea et al, 2020aD'Andrea et al, , 2020b, raising concern about their persistence under warmer and drier conditions (Noce et al, 2017). However, other studies point out opposite results (Tegel et al, 2014) or emphasize the swift recovery ability of beech after drought episodes (Vanhellemont et al, 2019).…”
Section: Impact On Nppmentioning
confidence: 57%
“…A.1). These phenological changes and particularly budburst advances could be problematic as they increase the risk of late frost events during the tree leafing (Ma et al, 2019;Zohner et al, 2020b), for which oak and beech are particularly sensitive (San-Miguel-Ayanz et al, 2016;D'Andrea et al, 2020a;D'Andrea et al, 2020b).…”
Section: Impact On Vegetation Periodmentioning
confidence: 99%
“…This is possibly due to high soil water retention and tree rooting depth in the study site. In any case, previous studies have shown a reduced impact of summer drought on the growth of southern beech forests, probably resulting from a shortening of the radial growth period, so that most of the growth is concentrated in the wettest period (spring and early summer), thus reducing the possible impact of summer droughts (D'Andrea et al 2020(D'Andrea et al , 2021. These results would confirm that trees in rear-edge populations can display a high resistance to drought (Cavin andJump 2017, but see Camarero et al 2021), although they could be particularly vulnerable to other climate extremes, such as spring frosts, particularly under continental conditions.…”
Section: Discussionmentioning
confidence: 95%
“…In line with this, the availability of non-structural carbohydrates is probably not a reason for lower resilience (Rs) of F. sylvatica. Previous studies showed a reduced impact of late frosts on non-structural carbohydrate concentrations of F. sylvatica (Rubio-Cuadrado et al 2021); when a significant impact occurs this is rapidly reversed (D'Andrea et al 2019(D'Andrea et al , 2021. In addition, the lower proportion of parenchyma and non-structural carbohydrate concentrations in the sapwood of F. sylvatica as compared with that of the two Quercus species may be compensated by a higher sapwood depth (Rodríguez-Calcerrada et al 2015).…”
Section: Frost Legacies: Decreasing Resistance Index and Delayed Sene...mentioning
confidence: 90%
“…These findings suggest that mechanisms of drought-induced tree mortality interact with seasonality in temperate forest ecosystems. In addition, C accumulation in trees only occurs in the growing season, which is critical for the survival and regrowth of trees in the following seasons (Tixier et al, 2019 ; D'Andrea et al, 2021 ). However, most of the studies generally focus on the response of hydraulic and C storage to drought conducted in growing seasons.…”
Section: Introductionmentioning
confidence: 99%